Nutritional Status in Patients with Chronic Pancreatitis - Kucheryavyy, Yuriy A.; Andreev, Dmitry N. (Journal of Nutritional Therapeutics, 2014)
Chronic pancreatitis (CP) is defined as a continuing inflammatory disease of the pancreas that is characterized by irreversible morphological changes often associated with pain and the loss of exocrine and/or endocrine function, which may be clinically relevant. Maldigestion (absolute deficiency of pancreatic enzyme secretion) is a typical complication of CP of any etiology with long anamnesis. Fat malabsorption is considered to be the malnutrition base in CP patients. The purpose of this article is to evaluate the role of nutritive status and nutritive deficiency in CP patients, evaluate diagnostic approaches, correct nutritive status deviation with reference to previous experience, and explore the present situation and possible future perspectives.